Estimation of the output deviation norm for uncertain, discrete-time nonlinear systems in a state dependent form - Orłowski, Przemysław (Zielona Góra: Uniwersytet Zielonogórski)
Numerical evaluation of the optimal nonlinear robust control requires estimating the impact of parameter uncertainties on the system output. The main goal of the paper is to propose a method for estimating the norm of an output trajectory deviation from the nominal trajectory for nonlinear uncertain, discrete-time systems. The measure of the deviation allows us to evaluate the robustness of any designed controller.
Keywords: uncertain systems; uncertain estimates; discrete-time systems; nonlinear systems